High voltage asymmetric converter for electrostatic particle accelerators - Diego Alberto Fanego; Orlando Silvio Sandini; Hernan Emilio Tacca; Andres Juan Kreiner (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
This work presents several topologies of asymmetric high voltage converters for electrostatic particle accelerators. The options are compared on the basis of their transfer functions and the magnetic components required, and the most suitable for the intended purpose is selected. Simulations and measurement results of the prototype, which has symmetrical voltage output and soft switching in the main transistor, are presented. The prototype built features output voltages of 10 kVand-10 kV, the converter uses a single common command ground for the transistors simplifying its drivers, and also by means of the presented snubber circuit it recovers energy during soft switching.